Enhance Decision Support Systems Method of Measure Student Levels and Attitude Cigarette Danger for Health Based on AHP - Fauzan Nurahmadi (Institute of Computer Science (IOCS), 2021)
This paper described about study determining the criteria in determining criteria and alternatives for student level knowledge of the dangers of smoking to health by the use of decision support systems so that it is easier to determine criteria by using selection methods that make it easy to obtain information on a system built to manage data- data so as to make it easy for users and can produce clear and accurate information and can produce reports that are expected to help teachers, and principals in making and making the right decisions later.